Combined intravitreal methotrexate and immunochemotherapy followed by reduced‐dose whole‐brain radiotherapy for newly diagnosed B‐cell primary intraocular lymphoma. (12th July 2017) - Kaburaki, Toshikatu; Taoka, Kazuki; Matsuda, Junko; Yamashita, Hideomi; Matsuda, Izuru; Tsuji, Hideki; Tanaka, Rie; Nakazaki, Kumi; Nakamura, Fumihiko; Kamiya, Kohei; Kurokawa, Mineo; Ohtomo, Kuni; et al.
Summary: Primary intraocular lymphoma (IOL) has a propensity for central nervous system (CNS) relapse within 2 years of initial diagnosis, affecting clinical outcome. To reduce CNS relapse, we performed the combination treatment protocols of intravitreal methotrexate injections, methotrexate‐based systemic induction chemotherapy and consolidation high‐dose cytarabine and reduced‐dose whole brain radiation therapy (rdWBRT, 23·4 Gy) for B‐cell primary IOL with or without newly diagnosed CNS involvement. All patients underwent longitudinal brain magnetic resonance imaging (MRI) and cognitive assessment for evaluation of treatment‐induced leucoencephalopathy. Seventeen patients initiated and 16 completed the protocol treatment. CNS relapse occurred in 2 patients and intraocular relapse in 3. Four‐year progression‐free survival (PFS) was 74·9% and 4‐year overall survival (OS) was 86·3%, with a median follow‐up period of 48·9 months. Of 11 patients without CNS involvement, 1 had CNS relapse and 3 intraocular relapse, and 4‐year PFS and OS was 72·7% and 88·9%, respectively. Although white matter abnormalities shown by MRI were significantly increased at 4 years after rdWBRT, only one patient developed mild cognitive impairment. The combination of intravitreal chemotherapy, prophylactic systemic chemotherapy and rdWBRT for primary IOL showed a potential to reduce CNS relapse rate and improved 4‐year PFS and OS without increase of cognitive dysfunction.